Strength, power, and muscular endurance exercise and elite rowing ergometer performance - Lawton, T. W.; Cronin, J. B.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2013)
Knowledge of the relationship between weight room exercises and various rowing performance measures is limited; this information would prove useful for sport-specific assessment of individual needs and exercise prescription. The purpose of this study was to establish strength, power, and muscular endurance exercises for weight room training, which are strong determinants of success in specific performance measures used to assess elite rowers. Nineteen heavyweight elite males determined their repetition maximum (RM) loads for exercises using a Concept 2 DYNO [5, 30, 60 and 120RM leg pressing and seated arm pulling (in Joules)] and free weights [1RM power clean (in kilograms) and 6RM bench pull (in kilograms and watts)]. Rowing performance measures included a 7-stage blood lactate response ergometer test (aerobic condition), time trials (500, 2000, and 5000 m), a peak stroke power test, and a 60-minute distance trial. Pearson correlation moments (r > 0.7) and stepwise multiple linear regression calculations (R2 > 50%) were used to establish strong common variances between weight room exercises and rowing ergometer performance (p < 0.05). Weight room exercises were strong predictors of 2000-m, 500-m time (in seconds), and peak stroke power performance measures only. Bench pull power (in watts) and 1RM power clean (in kilograms) were the best 2-factor predictors of peak stroke power (R2 = 73%; standard error of the estimates [SEE] = 59.6 W) and 500 m (R2 = 70%; SEE = 1.75 seconds); while 5RM leg pressing (in Joules) and either 6RM bench pull (kg) or 60RM seated arm pulling (in Joules) the best predictors of 2000 m (R2 = 59%; SEE = 6.3 seconds and R2 = 57%; SEE = 6.4 seconds, respectively). Recommended exercises for weight room training include a 1RM power clean, 6RM bench pull, 5RM leg press, and 60RM seated arm pulling.